Przemiany metanu w środowiskach torfowych - Stępniewska, Zofia; Goraj, Weronika; Kuźniar, Agnieszka (Leśne Prace Badawcze, 2014)
Wetlands and particularly peatlands are the main natural source of methane. Data indicate that 10–45% of methane emission comes from these sources. Methane emission from wetlands is the result of the balance between methanogenesis and methanotrophic processes and is actively affected by the wetland plant community composition. There are many factors affecting the balance of CH 4 : for instance, vegetation has a strong effect on CH 4 emissions from wetland ecosystems by influencing methane production, consumption and transport in the soil. The effects of plants on methane fluxes may be mediated by: molecular diffusion, internal transport through plant aerenchyma tissues and ebullition. Methane is formed in the process of methanogenesis under anaerobic conditions. It may then be emitted into the atmosphere directly from the soil or by internal transport through the plant. Alternatively, it may undergo methane oxidation by methanotrophic bacteria, both free-living in the root zone and associated with the host plant in symbiosis. Sphagnum moss is of particular importance for this processes as it contains methanotrophic bacteria in its endophytic system. Methanotrophic bacteria live inside the dead hyaline cells or on the surface of Sphagnum leaves and are able to oxidise methane produced in the soil during methanogenesis, making peatlands a natural biofilter for methane, one of the main greenhouse gases.